Strengthening Judicial Commission Authority in Indonesia Judicial Power Institutions, Link to Trias Politica Theory - Yoyon Mulyana Darusman; Elmer Micu Soriano; Bhanu Prakash Nunna (Faculty of Law, Universitas Jenderal Soedirman, 2024)
The People’s Consultative Assembly amended the 1945 Constitution to improve various aspects related to Indonesia's downturn. One crucial demand is improvement in law enforcement so that it is more independent from the interference of other powers outside the judiciary. The practice of judicial power in the New Order era was carried out under two institutional roofs. Powers relating to judicial processes and law enforcement in the courts were under the roof of the Supreme Court, while powers relating to the budget in the judicial process were under the roof of the Ministry of Justice. The 3rd amendment to the 1945 Constitution has placed the Supreme Court and the Constitutional Court as holders of judicial powers and the Judicial Commission as stipulated in Article 24 of the 1945 Constitution. It has placed the Judicial Commission as an institution with the authority to supervise judges, as Article 24 B of the 1945 Constitution stipulated. The research method uses a normative approach with a qualitative research model. The model of qualitative research is an approach to implementing research purposed toward natural phenomena or symptoms. Results of this research show there has been an imbalance in position between the Supreme Court, the Constitutional Court, and the Judicial Commission, which, in the end, the supervisory function of judges, which is the task of the Judicial Commission, becomes less than optimal and needs to be strengthened.